Current advances, research needs and gaps in mycotoxins biomonitoring under the HBM4EU : lessons learned and future trends - Alvito, Paula; Assunção, Ricardo; Bajard, Lola; Martins, Carla; Mengelers, Marcel J. B.; Mol, Hans; Namorado, Sónia; van den Brand, Annick D.; Vasco, Elsa; Viegas, Susana; Silva, Maria João (MDPI, 2022)
Mycotoxins are natural metabolites produced by fungi that contaminate food and feed worldwide. They can pose a threat to human and animal health, mainly causing chronic effects, e.g., immunotoxic and carcinogenic. Due to climate change, an increase in European population exposure to mycotoxins is expected to occur, raising public health concerns. This urges us to assess the current human exposure to mycotoxins in Europe to allow monitoring exposure and prevent future health impacts. The mycotoxins deoxynivalenol (DON) and fumonisin B1 (FB1) were considered as priority substances to be studied within the European Human Biomonitoring Initiative (HBM4EU) to generate knowledge on internal exposure and their potential health impacts. Several policy questions were addressed concerning hazard characterization, exposure and risk assessment. The present article presents the current advances attained under the HBM4EU, research needs and gaps. Overall, the knowledge on the European population risk from exposure to DON was improved by using new harmonised data and a newly derived reference value. In addition, mechanistic information on FB1 was, for the first time, organized into an adverse outcome pathway for a congenital anomaly. It is expected that this knowledge will support policy making and contribute to driving new Human Biomonitoring (HBM) studies on mycotoxin exposure in Europe.
Keywords: human biomonitoring; risk assessment; HBM4EU; human health; mycotoxins exposure; deoxynivalenol (DON); fumonisin B1 (FB1)